Analisis Penerapan Sistem Teknologi Informasi Terhadap Kinerja Pelaporan Aset Pada Pemerintahan Daerah - Gunawan, Hendra (Movere Journal, 2024)
The study aims to analyze the impact of the application of information technology (IT) systems on the quality of asset reporting performance in local government. Through a qualitative and quantitative approach, the study gathers data from various local governments that have implemented IT systems in their asset reporting process. Methods used include document analysis, surveys of government officials, as well as in-depth interviews with relevant stakeholders. The main objective of this study is to identify factors that influence the effectiveness of the application of IT systems in asset reporting, as well as to measure their impact on the efficiency, accuracy, and transparency of the reporting process. The results of the research show that the implementation of the IT system significantly improves the quality of asset reporting performance in the regional government. Key findings include improvements in data accuracy, time efficiency, and improved accessibility of asset information. However, the study also identifies several challenges, including resistance to change, resource constraints, and the need for technical training for staff.